Métodos para projeto de protótipos: um estudo de caso - Frederico Allevato Ramalho Filho (2007)
This monograph demonstrates how a set of methodologies can modify the design. Using these tools on prototypes and robotics has not been totally explored, and the research of the impact of both fields on the design is the subject of this study. In these case studies, the use of manufacturing and assembly optimization tools (DFMA), along with laminate object modeling (LOM) in the rapid manufacturing (RM) context, resulted in better quality, packaging, lower price and faster manufacturing.